2022
DOI: 10.15587/1729-4061.2022.267032
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation and modelling of residual stresses in face milling of Al-6061-T3 using neural network

Abstract: Milling process is a common machining operation that is used in the manufacturing of complex surfaces. Machining-induced residual stresses (RS) have a great impact on the performance of machined components and the surface quality in face milling operations with parameter cutting. The properties of engineering material as well as structural components, specifically fatigue life, deformation, impact resistance, corrosion resistance, and brittle fracture, can all be significantly influenced by residual stresses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Jiang [8] et al verified experimental data on residual stresses in the feed direction and perpendicular to the feed direction through finite element simulation, finding that residual stresses are non-uniform in different circular machining regions, residual tangential stresses are influenced by the cutting thickness, and residual stress distribution can be optimized through high-speed milling to control feed rate and tool diameter. Basma [9] et al studied and optimized the effects of cutting speed, feed rate and cutting depth on surface roughness of 6061-T3 aluminum alloy, and analyzed and simulated residual stresses by using an artificial neural network. The results showed that more residual stresses are generated under high cutting speeds, moderate feed rates and deeper cutting in the milling process.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang [8] et al verified experimental data on residual stresses in the feed direction and perpendicular to the feed direction through finite element simulation, finding that residual stresses are non-uniform in different circular machining regions, residual tangential stresses are influenced by the cutting thickness, and residual stress distribution can be optimized through high-speed milling to control feed rate and tool diameter. Basma [9] et al studied and optimized the effects of cutting speed, feed rate and cutting depth on surface roughness of 6061-T3 aluminum alloy, and analyzed and simulated residual stresses by using an artificial neural network. The results showed that more residual stresses are generated under high cutting speeds, moderate feed rates and deeper cutting in the milling process.…”
Section: Introductionmentioning
confidence: 99%